Analyzing Consumer Preferences for Local Products Integrating Social and Environmental Value Dimensions: A Choice Modelling Approach - Ali Hardana; Tata Putri Salsabila; Intan Septiana Hadi; Muhammad Esa Saputro Priyono; Camelia Adinda Putri; Tri Agnesa (CV. Get Press Indonesia, 2025)
This study investigates how growing consumer awareness of social and environmental issues influences preferences for local products in Indonesia. It analyzes consumer choices by integrating social, environmental, and economic values using a quantitative choice modeling approach. Based on nationally representative data from a 2023 survey of over 500 respondents, the research reveals that all three value dimensions significantly impact consumer decisions. Social attributes, particularly, strengthen consumer-brand relationships as consumers increasingly view local products not merely as functional goods but as an extension of the social and ethical values they wish to support. Furthermore, the findings show significant geographical heterogeneity: Urban consumers are more responsive to environmental attributes, whereas rural consumers prioritize the local social and economic value (Sukmana et al., 2024). Younger, highly educated, and urban consumers also show a greater willingness to pay a premium (8–12%) for products with sustainable attributes. These findings underscore the importance of segmented marketing strategies tailored to specific geographic contexts and provide actionable insights for policymakers and marketers to promote sustainable consumption and product development by fostering value-congruent brand loyalty.